The effect of an antibacterial mixture and non-instrumentation endodontic treatment in primary teeth: A systematic review and meta-analyses - Nabras Alrayes; Yara Almaimouni; Abrar Tounsi; Khalid Tarabzouni; Faisal Alonaizan; Maria Salem Ibrahim (Elsevier, 2023)
Studies assessing the clinical and radiographic success of LSTR in terms of the presence of pain, mobility, swelling, fistula/sinus tract, interradicular radiolucency, and root resorption have not been performed. We therefore performed a systematic review with the aim of evaluating the effectiveness of lesion sterilization and tissue repair (LSTR), using three antibacterial mixtures (3Mix), in treating primary teeth. Well-defined search strategies developed for four electronic databases, Web of Science, OVID, PubMed, and Scopus, were used in this study. Two independent reviewers selected relevant articles from 3,232 studies by screening titles and abstracts. Based on the inclusion criteria, 25 articles were selected. Eight analyses of clinical and radiographic results were conducted based on 6, 12, 18, and 24-month follow-up intervals. Data extraction and quality appraisal were performed by three independent reviewers. The composition of antibiotic mixtures used for LSTR varied substantially, with inconsistent radiographic and clinical success rates across the included studies. A quantitative grouping of the studies showed no significant differences between 3Mix and the control medicaments regarding radiographical and clinical success (p-value > 0.05). The available evidence on different LSTR using 3Mix is scarce, and the study findings were inconsistent. Therefore, additional clinical trials on 3Mix with different compositions are needed.